PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 064976 MEDAN TEMBUNG T.A 2024/2025 - Dina Maimunah HS Siregar; Apiek Gandamana; Irsan Rangkuti; Eva Betty Simanjuntak; Elvi Mailani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aimed to determine the effect of the Discovery Learning model on the mathematics learning outcomes of fourth-grade students at SDN 064976 Medan Tembung in the 2024/2025 academic year. It was an experimental study using a quantitative approach and a quasi-experimental method with a nonequivalent control group design. The population consisted of 45 fourth-grade students, with class IV-A (23 students) as the experimental group and class IV-B (22 students) as the control group. Data were collected through tests and observations. The research instrument involved pretests and posttests, which were validated through validity, reliability, difficulty level, and discriminating power tests. The results showed that students taught without the Discovery Learning model scored an average of 72.50, while those taught using the model scored 77.39. Data analysis included normality, homogeneity, and hypothesis tests. The normality test showed that the data were normally distributed with Sig. values of 0.200 (pretest) and 0.158 (posttest), both > 0.05. The homogeneity test yielded a Sig. value of 0.663 > 0.05, indicating homogeneous data. The hypothesis test using the t-test resulted in a Sig. (2-tailed) value of 0.046 < 0.05 and t-count (2.058) > t-table (2.017) at a significance level of α = 0.05. These results indicate that Ha is accepted and Ho is rejected. Therefore, the Discovery Learning model significantly affects mathematics learning outcomes of fourth-grade students at SDN 064976 Medan Tembung.